Orthorhombic Lithium Titanium Phosphate as an Anode Material for Li-ion Rechargeable Battery. (20th August 2015) - Kee, Yongho; Dimov, Nikolay; Minami, Keita; Okada, Shigeto
Highlights: Li-rich orthorhombic lithium titanium phosphate (OLTP) has been synthesized via a sol-gel route. OLTP adopts a different space group from the previously reported rhombohedral lithium titanium phosphate (RLTP) and shows solid-solution charge/discharge curves. OLTP shows higher Li + diffusivity and electrical conductivity, which makes it an attractive alternative for RLTP. Abstract: Rhombohedral lithium titanium phosphate, LiTi2 (PO4 )3, has been considered a suitable anode material for aqueous lithium-ion batteries. However, the electrochemical behaviors of pure lithium-rich polymorphs have not been described yet even Li-rich phase may show better electrochemical properties than conventional LiTi2 (PO4 )3 at the expense of somewhat lowered capacity. We have synthesized orthorhombic Li1.5 Ti2 (PO4 )3 (OLTP) and rhombohedral LiTi2 (PO4 )3 (RLTP) via sol-gel reactions and studied their fundamental electrochemical properties using galvanostatic charge/discharge and cyclic voltammetry (CV). Their feasibility as anode materials in LiFePO4 //Lix Ti2 (PO4 )3 configurations using aqueous electrolytes were also considered. The faster kinetics of the orthorhombic lithium titanium phosphate in this study were attributed to higher Li + diffusivity and electrical conductivity, making this material an attractive alternative for conventional rhombohedral LiTi2 (PO4 )3 .